Faraday waves and droplets in quasi-one-dimensional Bose gases - Tomio, Lauro [UNESP]; Gammal, A.; Abdullaev, F. Kh; Kumar, R. K. [UNESP]; IOP Publishing (Iop Publishing Ltd, 2020)
Faraday waves (FW) are studied in mixtures of Bose gases by taking into account quantum fluctuations beyond the GP mean-field formalism with the Lee-Huang-Yang term, with both inter- and intra-species scattering lengths periodically varying in time. In this case, the effect of periodic modulations on the system is studied, with nonlinear resonances shown to be excited in the oscillation widths of quantum droplets. It was shown that the period of the Faraday patterns is quite sensitive to the estimated value obtained by the beyond meanfield contribution, which can be used to measure quantum fluctuations in the ground state of the quasi-one-dimensional mixture. Variational predictions are confirmed by full numerical simulations. We also add an analysis of quantum droplets and quantum fluctuation contributions when considering three-body interactions.